2016
DOI: 10.1111/ajt.13456
|View full text |Cite
|
Sign up to set email alerts
|

Discarded Human Thymus Is a Novel Source of Stable and Long-Lived Therapeutic Regulatory T Cells

Abstract: Regulatory T cell (Treg)-based therapy is a promising approach to treat many immune-mediated disorders such as autoimmune diseases, organ transplant rejection, and graft-versus-host disease (GVHD). Challenges to successful clinical implementation of adoptive Treg therapy include difficulties isolating homogeneous cell populations and developing expansion protocols that result in adequate numbers of cells that remain stable, even under inflammatory conditions. We investigated the potential of discarded human th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 62 publications
5
70
0
Order By: Relevance
“…Though the graft could not be fully rescued due to the high immunogenicity of the skin transplant, these numbers were enough to prolong graft acceptance by thymic APC-induced allo-iTregs. Two recent reports are supporting our finding, where one showed that Nrp1 + Tregs generated in the thymus could suppress skin graft rejection and another stated human thymus to be an important source of stable and suppressive Foxp3 + Tregs for clinical therapeutics [50, 51]. …”
Section: Discussionsupporting
confidence: 87%
“…Though the graft could not be fully rescued due to the high immunogenicity of the skin transplant, these numbers were enough to prolong graft acceptance by thymic APC-induced allo-iTregs. Two recent reports are supporting our finding, where one showed that Nrp1 + Tregs generated in the thymus could suppress skin graft rejection and another stated human thymus to be an important source of stable and suppressive Foxp3 + Tregs for clinical therapeutics [50, 51]. …”
Section: Discussionsupporting
confidence: 87%
“…We recently explored the feasibility of an alternate source of naive T regs : pediatric thymuses. These organs are routinely removed during pediatric cardiac surgeries and are well suited for cell therapy applications . A major advantage of using the thymus as a source of T regs is the abundance of these cells: on average, 1–2% of thymocytes are CD4 + CD25 + T regs , translating to ~500 × 10 6 cells, ×100 more than in a single UCB unit and exceeding the number in the peripheral blood of an adult .…”
Section: Sources Of Tregsmentioning
confidence: 99%
“…However, there are more Tregs cells in a child's thymus than in an adult's entire blood volume and 100 times more than in a unit of cord blood, making it a very interesting source. 164 Nevertheless, this source requires a very complex organization between surgical teams and teams of biologists to collect the thymus and extract the cells and the Treg product would be from allogeneic sources to the recipient.…”
Section: Ne W Source S Of Treg S: D Ifferentiati On From Plurip Otementioning
confidence: 99%
“…To cope with the lack of persistence of the infused Tregs, we could multiply the injections of CD8 + Tregs as in CD4 + Treg-based clinical trials (RSMU-001: NCT01446484, Treg: NCT01624077, NCT02749084). However, there are more Tregs cells in a child's thymus than in an adult's entire blood volume and 100 times more than in a unit of cord blood, making it a very interesting source 164. Long-term culture and stable cryopreservation of CD8 + Tregs are possible 3.…”
mentioning
confidence: 99%